Identification and genetic analysis of the APOSPORY locus in Hypericum perforatum L. - Schallau, Anna; Johnston, Amal Joseph; Kőszegi, Dávid; Blattner, Frank R. (The plant journal, 2010)
The introduction of apomixis - seed formation without fertilization - into crop plants is a long-held goal of breeding research, since it would allow for the ready fixation of heterozygosity. The genetic basis of apomixis, whether of the aposporous or the diplosporous type, is still only poorly understood. Hypericum perforatum (St John’s wort), a plant with a small genome and a short generation time, can be aposporous and/or parthenogenetic, and so represents an interesting model dicot for apomixis research. Here we describe a genetic analysis which first defined and then isolated a locus (designated HAPPY for Hypericum APOSPORY) associated with apospory. Amplified fragment length polymorphism (AFLP) profiling was used to generate a cleaved amplified polymorphic sequence (CAPS) marker for HAPPY which co-segregated with apospory but not with parthenogenesis, showing that these two components of apomixis are independently controlled. Apospory was inherited as a dominant simplex gene at the tetraploid level. Part of the HAPPY sequence is homologous to the Arabidopsis thaliana gene ARI7 encoding the ring finger protein ARIADNE7. This protein is predicted to be involved in various regulatory processes, including ubiquitin-mediated protein degradation. While the aposporous and sexual alleles of the HAPPY component HpARI were co-expressed in many parts of the plant, the gene product of the apomict’s allele is truncated. Cloning HpARI represents the first step towards the full characterization of HAPPY and the elucidation of the molecular mechanisms underlying apomixis in H. perforatum.